The 4s Conceptual Model Based On Hermeneutics And Exegesis Of Proverbs 30:24–28: Implications For Contemporary Christian Financial Stewardship - Wibiksono, Tomy (Journal Research of Social Science, Economics, and Management, 2025)
Amid growing concerns over financial illiteracy and the declining integration of spiritual values in modern Christian economic life, this study constructs a conceptual model of Christian personal financial stewardship based on a symbolic exegesis of Proverbs 30:24–28. The passage presents four small creatures—the ant, rock hyrax, locust, and lizard—commended for their wisdom. These animals are interpreted as archetypes that embody key principles of financial stewardship. The study aims to develop a biblically grounded and theologically relevant framework for personal financial ethics in the Christian context. Utilizing a qualitative-reflective approach within practical theology, the research employs grammatical-historical exegesis in conjunction with symbolic-narrative hermeneutics, informed by the works of Osborne, Ricoeur, and Vanhoozer. The findings reveal four theological pillars: Sense Strategy (ant), which emphasizes financial awareness of seasonal rhythms; Shield Stewardship (rock hyrax), which promotes ethical and moral safeguarding; System Discipline (locust), which represents internal financial order; and Shift Scaling (lizard), symbolizing adaptive and incremental growth. These dimensions are synthesized into the 4S Conceptual Model and aligned with modern financial theories such as the Life-Cycle Hypothesis, Precautionary Saving, Behavioral Finance, and Adaptive Financial Resilience. The model offers a transformative framework that bridges biblical wisdom and contemporary financial practice. Its implications extend to discipleship, church education, marketplace ministries, and the spiritual formation of financial life.